A new species of Microhyla (Anura: Microhylidae) from Sri Lanka: an integrative taxonomic approach - Wijayathilaka, Nayana; Garg, Sonali; Senevirathne, Gayani; Karunarathna, Nuwan; Biju, S.d.; Meegaskumbura, Madhava (Zootaxa, 2016)
Species boundaries of Microhyla rubra of India and Sri Lanka were assessed using the following criteria: genetic barcoding, morphology, and vocalization. We use a ca. 500 bp fragment of the 16S rRNA mitochondrial gene and show that there is an uncorrected pairwise distance of 2.7−3.2% between the Indian and Sri Lankan populations of M. rubra. We show that they are different in several call characteristics such as, dominant frequency, call duration, call rise time and pulse rate. Morphologically, the Sri Lankan population can be distinguished from the typical M. rubra described from southern India, by a combination of characters: body size, skin texture, and feet dimensions. We recognize the population from Sri Lanka as a new species, Microhyla mihintalei sp. nov., a widely distributed lowland species with an elevational distribution of up to 500 m a.s.l.